Advancing neurosurgery in Africa: the impact of telemedicine and capacity building - Abdulbasit Opeyemi Muili; Tangmi Djabo Eric Adrien; Aderinto Nicholas; Sanobar Shariff; Afolayan Oluwatosin Florence; Farah Awad; Taha Oseili (Egyptian Journal of Neurosurgery, 2025)
Abstract Neurosurgery in Africa is faced with numerous challenges, including inadequate infrastructure, a shortage of trained personnel, and limited access to specialized care. However, recent developments in telemedicine and capacity-building initiatives are providing opportunities to overcome these challenges and improve the delivery of neurosurgical care in Africa. Through teleconsultation and teleeducation programs, neurosurgeons in remote areas can receive expert advice and guidance from specialists in other parts of the world. This can improve the quality of care and reduce the need for patients to travel long distances to access it. Capacity-building initiatives, such as training programs for local healthcare workers and the establishment of neurosurgical centers of excellence, can also improve the quality of neurosurgical care in Africa. These initiatives can help to develop local expertise and increase the number of trained neurosurgeons, thereby increasing access to specialized care and reducing the burden of disease. This review discusses the impact of telemedicine and capacity-building initiatives on advancing neurosurgery in Africa. It highlights some of the successful programs and partnerships that have been established in recent years and provides examples of their impact on improving neurosurgical care in the region. It also discusses the challenges and opportunities for future research and collaboration in this area, with the aim of further improving access to high-quality neurosurgical care in Africa.